BIBLIOMETRIC ANALYSIS OF UNDERGRADUATE THESIS IN THE FACULTY OF VETERINARY MEDICINE, SAN MARCOS NATIONAL UNIVERSITY, IN THE PERIOD OF 2001-2006 - San Martín H., Felipe (2008)
Undergraduate thesis play a major role on research activities at the Veterinary Faculty of Universidad Nacional Mayor de San Marcos (FMV-UNMSM) and therefore, this study was planned to evaluate the research component through a bibliometric analysis of all theses that were defended during the 2001-2006 period. Analyzed data included the academic unit, discipline, animal species, adviser and thesis committee. Data was organized and normalized in the institutional database for recording scientific publications (REGULVS) and MS Excel was used to evaluate and build a matrix of coincidences using the macro Microsoft Excel Toolinf©. A total of 247 theses were registered with an annual average of 41. Canine (15.5%), bovine (15.5%), poultry (13.4%), swine (12.6%) and alpaca (11.3%) were the most studied species. Seventy five percent of the theses were in the area of Animal Health, and among them, Parasitology (64/247) and Epidemiology (46/247) were the most studied disciplines. The laboratories of Microbiology and Parasitology (37%), Avian Pathology (12%), Preventive Veterinary Medicine (8.5%), and Reproduction and Veterinary Obstetrics (7.7%) generated most of the theses. Three lecturers were responsible for 33% of the thesis and eight of them for 57%. Asymmetry was detected among the number of advisers and participants of theses committees, so corrective measures were recommended.